2011
DOI: 10.1016/j.jad.2010.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of major depressive episode correlates with elevation of substate region of residence

Abstract: Background Major depressive disorder (MDD) is a common disorder that is often associated with suicide. We have recently suggested that elevation may play a role in regional variations in rates of suicide. We hypothesize that there is also a significant correlation between incidence of MDD and elevation of residence. Methods The substate estimates from the 2004 to 2006 National Surveys on Drug Use and Health (NSDUH) report from SAMHSA was used to extract substate level data related to percentages of people 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…This finding has been independently replicated, using mortality data covering two decades (1979-1998) and 2,584 U.S. counties (Betz, Valley et al 2011; Brenner, Cheng et al 2011). We additionally found an association between altitude and depression (DelMastro, Hellem et al 2011). Comorbid depression and cocaine use disorder is a risk factor for relapse (Poling, Kosten et al 2007; Stulz, Thase et al 2011).…”
mentioning
confidence: 65%
“…This finding has been independently replicated, using mortality data covering two decades (1979-1998) and 2,584 U.S. counties (Betz, Valley et al 2011; Brenner, Cheng et al 2011). We additionally found an association between altitude and depression (DelMastro, Hellem et al 2011). Comorbid depression and cocaine use disorder is a risk factor for relapse (Poling, Kosten et al 2007; Stulz, Thase et al 2011).…”
mentioning
confidence: 65%
“…Chronic hypoxia in patients with respiratory or cardiac dysfunction could similarly precipitate depression (Katz, 1982). Residents at altitude are also prone to loss of appetite, disrupted sleep cycles (Maa, 2010) and increased depression (DelMastro et al, 2011;Gamboa, 2011), implying that low brain serotonin levels may be an issue here. Low brain serotonin is also linked to suicidal ideation and attempts ( Joiner et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that people living at altitude have higher levels of depression than those at sea level (Gamboa, 2011). Extraction of altitude-based data from U.S. national mental health surveys confirm that rates of MDD escalate significantly with elevation of residence (DelMastro et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Cocaine and other drug use, such as methamphetamines, have been shown to have an association with depression and mania in bipolar disorder and suicide. Recent studies suggest that the effects of hypoxia may cause an increase of DA that may contribute to these effects (DelMastro et al, 2011; Fiedler et al, 2012; Kim et al, 2011). …”
Section: Discussionmentioning
confidence: 99%